2009
DOI: 10.5004/dwt.2009.444
|View full text |Cite
|
Sign up to set email alerts
|

Transparent exopolymer particles: Potential agents for organic fouling and biofilm formation in desalination and water treatment plants

Abstract: A B S T R A C TTransparent exopolymer particles (TEP) are ubiquitous in marine and freshwaters, and have been subject to intensive study by oceanographers and limnologists over the past 15 years. These microscopic organic particles (visualized by Alcian Blue staining for acid polysaccharides) may be considered a planktonic form of exopolymeric substances (EPS). Two aspects relating to the potential involvement of TEP as important agents in organic fouling and biofilm formation on membranes in desalination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 41 publications
0
54
0
Order By: Relevance
“…The transparent exopolymer particles (TEPs) have been reported to be one of the main components of membrane biofilms (Bar-Zeev et al, 2009;Berman, 2010;Berman and Holenberg, 2005). TEPs are ubiquitous in all aquatic systems, and characterized as sticky substances mainly composed of acidic polysaccharides and stainable with alcian blue (Passow, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…The transparent exopolymer particles (TEPs) have been reported to be one of the main components of membrane biofilms (Bar-Zeev et al, 2009;Berman, 2010;Berman and Holenberg, 2005). TEPs are ubiquitous in all aquatic systems, and characterized as sticky substances mainly composed of acidic polysaccharides and stainable with alcian blue (Passow, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…They are, thus, about two to four orders of magnitude stickier than phytoplankton or mineral particles and have a high probability of coagulation or surface attachment upon collision (17,18). Therefore, TEPs are likely to play an important role in coating submersed surfaces and in the formation of aquatic biofilm (14,15,19).…”
mentioning
confidence: 99%
“…Recently, TEPs have been implicated as an important factor in the development of aquatic biofilm (2,14,15). Like the extracellular polymeric substances (EPSs) that form the matrix of microbial biofilms, these microgel particles are partly composed of polysaccharides with highly surface-active polymers of fucose and rhamnose (16).…”
mentioning
confidence: 99%
“…This may be due to the deformable nature of TEP, which allows it to pass through the pre-treatment system [8]. Indeed, studies have shown that TEP is not completely removed by pre-treatments such as microfiltration, ultrafiltration, and combined coagulation-sedimentation-rapid sand filtration [39,40].…”
Section: Tep Quantificationmentioning
confidence: 98%